1996
DOI: 10.3109/00365549609027157
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Line-Related Infection and Mechanical Failure of an Antiseptic Impregnated Central Venous Catheter in Highly Immunocompromised Patients

Abstract: Prolonged central venous catheterisation is associated with a substantial risk of line related infection, which may be reduced when a chlorhexidine/silver-sulfadiazine coated catheter (ARROWgard Blue(TM)) is used in medical or surgical ICU patients. However, no data is available from severely immunocompromised patients. We therefore performed an initial exploratory study among patients with haematological malignancy, aplastic anaemia or bone marrow transplantation. The study was terminated after the 12th cathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 6 publications
2
9
0
Order By: Relevance
“…The incidence of positive blood cultures observed in this study corresponds with previously reported incidence of CVC-related infections and positive blood cultures in hematological patients ranging between 35% and 52% [1,2,4,5,7,13]. A lower number of patients with positive CVC blood cultures in the coated CVC group (45% vs. 36%, p =0.05), more repeatedly positive CVC blood cultures observed in the uncoated CVC group (26% vs. 8,6%, p =0.018), and highly significant difference in positive CVC blood cultures per 1,000 catheter-days (29 vs. 14, p=0.005) showed rather positive effect of the chlorhexidine/silver sulfadiazine-coated CVCs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The incidence of positive blood cultures observed in this study corresponds with previously reported incidence of CVC-related infections and positive blood cultures in hematological patients ranging between 35% and 52% [1,2,4,5,7,13]. A lower number of patients with positive CVC blood cultures in the coated CVC group (45% vs. 36%, p =0.05), more repeatedly positive CVC blood cultures observed in the uncoated CVC group (26% vs. 8,6%, p =0.018), and highly significant difference in positive CVC blood cultures per 1,000 catheter-days (29 vs. 14, p=0.005) showed rather positive effect of the chlorhexidine/silver sulfadiazine-coated CVCs.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to the microbiologically documented infections in patients before hematopoietic engraftment of only 5-10%, the focus of bacterial infection can be identified in more than 50% of patients after hematopoietic engraftment [3,11,14]. The incidence of CVC-related infections in hematological patients has been reported to range between 35% and 45% [1,4,5,13] and positive blood cultures have been found in 36-52% [2,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the proportion of cases of infective endocarditis due to viridans group streptococci or enterococci was significantly lower than that in studies that have encompassed cases from the last 2 decades [26,27]. Our observations on the increasing prevalence of SA-NVIE reflect the probable convergence of 2 important trends: there is an increasing number of patients (e.g., geriatric patients and patients with transvenous pacemakers or indwelling catheters) who are at risk for endocarditis in general, and there is an increasing number of patients (e.g., patients with immunosuppression, diabetic patients, and persons undergoing hemodialysis) who are at risk for S. aureus bacteremia [8,16,[28][29][30]. Given that gram-positive organisms have now overtaken gram-negative pathogens as the most common cause of septicemia in the United States [31], it is likely that rates of SA-NVIE will continue to increase.…”
Section: Discussionmentioning
confidence: 59%
“…In literature, the incidence of catheter-related infection (CRI) ranges from 5 to 15% [41]. The incidence of CRI in haematologic-oncologic patients was also reported to range from 18 to 45% [11,25]. Infections associated with the use of central venous catheters can result in serious medical complications and expensive care [30].…”
mentioning
confidence: 99%